Review on Algae Biodiesel Production: A Strategy to Enhance Future - Sayak Ghosh; Priyadarshi Mukherjee (International Journal of Biochemistry and Biomolecule Research, 2023)
The quest for cleaner and renewable energy sources has propelled the interest in the production of biodiesel from algae. Algae, due to their high oil content and fast growth rate, present a promising feedstock for the production of biodiesel, especially since they can be cultivated on non-arable land and with seawater or wastewater. Algae biodiesel offers the advantage of being compatible with current diesel engines without any need for modification, compared to conventional diesel fuel. The process of producing biodiesel from algae involves the extraction of lipid oils from the algae and their subsequent transformation into biodiesel via transesterification. Algae biodiesel has several benefits over traditional diesel, including lower emissions and a reduced dependence on fossil fuels. To achieve optimal algae growth, the use of nutrient-rich mediums and favourable environmental conditions, such as appropriate lighting and temperature, are crucial. Despite its potential benefits, the production of source means algae for biodiesel faces major obstacles such as the high cost of algae culture and the development of effective harvesting and extraction techniques. However, with further research and development, the production of biofuel from algae has the potential to replace fossil fuels in a sustainable and practical manner. Looking towards the future, the continued advancement of algae cultivation and extraction techniques, coupled with increasing demand for clean energy, may lead to a more widespread adoption of algae biodiesel. Moreover, the use of algae for biofuels could contribute to sustainable development by providing an alternative to non-renewable energy sources and reducing greenhouse gas emissions. The potential of producing biodiesel from algae offers a promising avenue towards a more sustainable future.
Keywords: Bio-diesels; algae; fossil fuel; greenhouse gas emissions; sustainable future